Gender and Justice in Islamic Family Law: A Critical Analysis of Contemporary Discourse - Pramidazzura Alifa Rifqi (Journal of Nafaqah, 2025)
This article critically examines contemporary discourse on gender and justice in Islamic family law, focusing on the structural causes of persistent gender inequality within legally enforced family norms. Although Islamic law is normatively grounded in principles of justice and moral equality, prevailing interpretations of family law often reproduce patriarchal power relations through doctrines governing marriage, divorce, inheritance, and guardianship. This study identifies three core legal problems: normative ambiguity in defining gender justice within Islamic legal sources, interpretive dominance of formalistic classical fiqh over justice-oriented reasoning, and institutional resistance to gender-equitable reinterpretation. Employing a normative juridical method with statute, conceptual, and case approaches, the article analyzes codified Islamic family law, contemporary hermeneutical debates, and patterns of judicial reasoning. The analysis demonstrates that gender injustice persists not due to doctrinal necessity, but because ethical objectives of Islamic law are subordinated to hierarchical interpretive authority. This article argues for a prescriptive reconstruction of Islamic family law grounded in maqāṣid al-sharīʿah, emphasizing substantive justice rather than formal equality. It proposes recalibrating interpretive authority, reforming codified norms, and adopting gender-sensitive legal reasoning to restore the legitimacy and moral coherence of Islamic family law in contemporary societies.